Untapped potential: Cultural sensitivity-Islamic persuasive communication in health promotion programs - Ahmad, Mohd Khairie (2007)
The development of the health communication field has been paralleled with the appreciation of the importance of the social and cultural context in understanding health, health behaviour and health communication. This argues both for a shift in methods and a shift in the theoretical and philosophical approaches underpinning these methods.A lack of understanding of Muslims and their cultural and religious tradition contributes to potential conflicts in health promotion.Thus, this paper suggests the use of Islamic values and elements in developing a communication strategy for promoting health behavioural change.This paper has three objectives: (1) to briefly review the research on cultural sensitivity factors with specific focus on religious factors in health communication; (2) to identify the most promising explanatory mechanism for faith-based (Islamic) communication persuasion in health promotion, with particular attention to the relationship between religious factors and health behaviour; and (3) to critique previous work on Islamic communication and health, pointing out potential and promising new research directions in health promotion.These insights may contribute to further development of health promotion strategies for Muslims in Islamic nations as well as Muslim communities in non-Islamic nations through the inter-culturalisation process.